HOSPITAL INFANT MORTALITY IN THE RUSSIAN FEDERATION AND PERSPECTIVES FOR ITS REDUCTION - D.I. Zelinskaya; R.N. Terletskaya ("Paediatrician" Publishers LLC, 2007)
The researchers give the analysis findings of the hospital mortality indices among infants under 1 year old in the Russian federation within the period from 1993 to 2004. They provide the mortality structure in the obstetric in patient, newborn pathologies departments, as well as other in patient institutions. They showed that the hospital mortality among infants in the Russian federation is characterized by the continuous reduction. The unstable trends are marked in respect of newborn and infant mortality within the first 24 hours from the moment they arrive to the in patient department. Therefore, it is essential to develop the resuscitation services for the newborns. The reduction of the less than 24 hours mortality is possible only if the outpatient care for the infants under 1 year old is improved. Key words: infant mortality, hospital mortality, infants.